Exonic sequencing and MLH3 gene expression analysis of breast cancer patients - Khailany, Rozhgar A.; Ozaslan, Mehmet (Cellular and Molecular Biology, 2021)
Breast cancer is the most common cancer in women worldwide. Detection of breast cancer susceptibility genes is an important issue. Also, MLH3 is a DNA mismatch repair gene and mutation in this gene is harmful in different cancers. This study aimed to use exome sequencing to uncover previously undetected breast cancer-predisposing variants. Also, we investigated the MLH3 gene expression of breast cancer patients which can be a breast cancer susceptibility gene. A total of 80 samples including 40 paired normal and cancer tissue samples were collected at Zheen International Hospital, Erbil, Iraq. Exome sequencing was used to identify mutations. Different in silico tools were used to predict the effect of mutation on the structural features or protein function. Real-time PCR was used for assessing the expression of MLH3 in breast cancer patients. We identified 26 variants in breast cancer patients, 22 inherited variants were found in MLH3, CHECK2, BRCA1, BRCA2, BLM, TP53, MSH6, NBN and PTEN genes and 4 somatic variants were found in PALB2, RAD50 and RBM10 genes. It was found that the expression of the MLH3 gene in tumor samples was significantly down-regulated compared with normal tissues. Statistically, high significance was found. The decreased expression of MLH3 was significant in all ranges of ages and all breast cancer types. Also, the expression of MLH3 decreased significantly in patients with breast cancer grades of II and III. In conclusion, MLH3 can be used as a susceptibility gene especially in grades II and III of breast cancer.